Why Do I Seek Negative Feedback? Assessment Orientation, Self-Criticism, and Negative Feedback-Seeking - Liu, Zhaoyan; Yuan, Qinghong; Qian, Shanshan; Ellenberg, Molly; Kruglanski, Arie W. (Frontiers in Psychology, 2021)
Negative feedback plays an important role in employee performance improvement, yet little research has specifically examined the motivational factor that drives employees to seek negative feedback. Drawing from the regulatory mode theory, we propose that assessment orientation could increase negative feedback-seeking by triggering individual self-criticism and participative leadership could enhance this effect. Results from a two-wave lagged survey study obtained from 216 Chinese employees suggested that assessment orientation is positively correlated with negative feedback-seeking via the mediating role of self-criticism. Moreover, the positive effect of assessment orientation on self-criticism and the positive indirect effect of assessment orientation on negative feedback-seeking via self-criticism are both stronger when participative leadership is higher. These results enrich the literature on feedback-seeking and regulatory mode and are useful for increasing employee negative feedback-seeking behavior in the organization.